Influence of Chemical and Physical Change of Pollen Microgels on Swelling/De‐Swelling Behavior. Issue 21 (6th July 2020) - Fan, Teng‐Fei; Hwang, Youngkyu; Ibrahim, Mohammed Shahrudin; Ferracci, Gaia; Cho, Nam‐Joon
Abstract: Pollen, the male microgametophyte of seed plants, is commonly used as a food and health supplement. Here, a facile method to transform sunflower pollen into pH‐responsive microgels with tailored properties is presented. The structure and morphology of the pollen microgel are characterized by scanning electron microscopy, confocal laser scanning microscopy, and dynamic image particle analysis based on potassium hydroxide treatment with various incubation time and concentration. These pollen microgels exhibit significant volume change under different pH conditions and Ca + /ethylenediaminetetraacetic acid treatment. The results describe the fundamental properties of pollen microgels and pave the way for its future applications, such as "smart" drug carriers. Abstract : Sunflower pollen grains are transformed into soft materials, pollen microgels, for high processability by the soapmaking method. The physical and chemical properties of the sunflower pollen microgel are investigated for different potassium hydroxide concentrations and incubation times.